2002
DOI: 10.3177/jnsv.48.325
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Bioavailability of Vitamin B12-Compounds from Edible Algae.

Abstract: SummarySubstantial amounts of vitamin B12 were found in some edible algae (green and purple layers) and algal health food (chlorella and spirulina tablets) using the Lactobacillus delbrueckii subsp. lactis ATCC7830 microbiological assay method. Corrinoid compounds were purified and characterized from these algae to clarify the chemical proper ties and bioavailability of the algal vitamin B12. True vitamin B12 is the predominate cobamide of green and purple layers and chlorella tablets. Feeding the purple layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 32 publications
3
64
0
1
Order By: Relevance
“…Vitamin B12 from microalgae in Chlorella sp. has better bioavailability than Spirulina microalgae [87]. Vitamin B12 deficiency can cause neurological and psychiatric problems, due to its importance for neurological function and also for a proper red blood cell formation and DNA synthesis.…”
Section: Vitaminsmentioning
confidence: 99%
“…Vitamin B12 from microalgae in Chlorella sp. has better bioavailability than Spirulina microalgae [87]. Vitamin B12 deficiency can cause neurological and psychiatric problems, due to its importance for neurological function and also for a proper red blood cell formation and DNA synthesis.…”
Section: Vitaminsmentioning
confidence: 99%
“…The bioavailability of vitamin B12-compounds from spirulina (and chlorella) was evaluated using vitamin B12-deficient rats [7]. The results suggested that algal vitamin B12 is a bioavailable source for mammals.…”
Section: Spirulina (Athrospira Platensis and Arthrospira Maxima) Nutrmentioning
confidence: 99%
“…Spirulina platensis (S. platensis), which belongs to the class of Cyanophyceae and family of Oscillatoriaceae according to the taxonomic categories, contains high concentrations of bioactive components such as c-linolenic acid [3,4], antioxidants [5][6][7], phycobiliprotein, and vitamins [8][9][10]. Due to these components, S. platensis has a great potential for applications as functional health foodstuff.…”
Section: Introductionmentioning
confidence: 99%